Cu-based ester hydrogenation catalyst prepared by multi-step method and application thereof
The Cu-based ester hydrogenation catalyst was prepared by a multi-step method, and the interaction between different functional additives and Cu was solved, and the existing catalysts were achieved with high selectivity and conversion rate 1,3-propylene glycol production.
Patent Information
- Application Number
- CN202510110672.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-15
AI Technical Summary
The existing catalysts have low activity, poor stability, and low selectivity of 1,3-propanediol in the hydrogenation reaction of 3-hydroxypropionate.
A multi-step method is used to prepare Cu-based ester hydrogenation catalysts. Through the interaction of different functional additives with Cu, a multi-composite catalyst with strong interaction is formed to regulate Cu's reduction ability and species state.
The stability and catalytic performance of the catalyst are significantly improved, and the selectivity and conversion rate of 1,3-propylene glycol are improved.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalytic preparations, and in particular relates to a Cu-based ester hydrogenation catalyst prepared by a multi-step method and application thereof. Background Art
[0002] 1,3-Propanediol (1,3-PDO) is a colorless, odorless, transparent liquid that is miscible with water, alcohol, and a variety of organic solvents, and has the typical properties of alcohols and diols. The main use of 1,3-PDO is as a polymer material with excellent performance in the synthesis of polymer monomers, replacing ethylene glycol and butanediol to produce polyol polyesters, and used to manufacture new polyester fibers PTT with excellent performance, which are then used in clothing, carpets, electronics, automobiles and other markets. With the further maturity of PTT fiber production technology and the further reduction of costs, PTT can gradually replace 5-10% of traditional polyester fibers at a reasonable price difference, and the market prospects are very broad. Among them, 1,3-PDO is the core key raw material for the synthesis of PTT and is irreplaceable.
[0003] At present, the methods for preparing 1,3-propylene glycol are mainly divided into two types: chemical synthesis and biological fermentation. Among them, the methods for preparing 1,3-propylene glycol by chemical synthesis include the EO method and the acrolein hydration method. The EO method, also known as the ethylene oxide carbonyl synthesis method, is mainly divided into two process routes, namely, the ethylene oxide hydroformylation method and the ethylene oxide hydroesterification method. Among them, the ethylene oxide hydroesterification method has low raw material costs, the intermediate product is not easy to self-polymerize, and it is easy to scale up the process to achieve large-scale production. In addition, the intermediate 3-hydroxypropionic acid methyl ester in this method is more stable than the intermediate 3-hydroxypropanal in the ethylene oxide hydroformylation method, and because the β-hydroxyl group in 3-hydroxypropionic acid methyl ester is easier to remove than the ester hydrogenation, creating more and more suitable ester hydrogenation active sites will greatly improve the selectivity of the main product 1,3-propylene glycol.
[0004] In recent years, copper-based catalysts have become the first choice for the hydrogenation of 3-hydroxypropionic acid methyl ester to prepare 1,3-propylene glycol because of their low production cost and the advantages of high activity, high selectivity, mild reaction conditions, and good anti-toxicity when combined with other active additives. The addition of additives in multi-component catalysts can play a role in particle dispersion and stabilization of active Cu species. Patent CN101993352A reports that a multi-component metal oxidation catalyst is prepared by coprecipitation using oxides of Cu, Mn and Zr as active components. The active components of the catalyst are evenly distributed, which can inhibit the occurrence of dehydration side reactions, thereby improving the selectivity of the product and having good reaction performance and stability. Patent CN103721734A reports that copper oxide is used as the active main component, active additives such as manganese oxide, molybdenum oxide, and phosphorus pentoxide are added, and silicon dioxide is used as a catalyst carrier, which can realize the hydrogenation reaction of high-concentration 3-hydroxypropionic acid methyl ester to prepare 1,3-propylene glycol, significantly improving the product conversion rate and selectivity. Patent CN102059125A reports a catalyst for hydrogenating methyl 3-hydroxypropionate to prepare 1,3-propylene glycol. The active components of the catalyst are oxides of Cu, Mn and Zr. It is prepared by titration with an alkaline precipitant of sodium carbonate or sodium hydroxide, and has the advantages of high activity, high repeatability and mild conditions. Patent CN114345339B reports a supported binary metal catalyst including a main metal Cu, an auxiliary metal M, and a SiO2 carrier. The surface hydroxyl groups of SiO2 are replaced by metal oxygen bonds through the reaction of an alkoxy metal compound and an alkylsilanol. The catalyst is used for the hydrogenation of methyl 3-hydroxypropionate to prepare 1,3-propylene glycol. The conversion rate can reach 90-100%, and the selectivity of 1,3-propylene glycol can reach 70-85%. Patent CN107303488B reports that an ester hydrogenation catalyst is prepared by a precipitation method. The catalyst includes 5 to 30% (wt) active ingredients, 0.1 to 2.5% (wt) additives and a carrier. The active ingredient is a Cu-Ag alloy, the additive includes one or more of B, C, N, F, Cl or Br, and the carrier is a composite oxide of r-Al2O3 and SiO2. Compared with the prior art, the present invention has the characteristics of high activity, high product directional selectivity and good stability, and is particularly suitable for industrial applications.
[0005] The research results of existing patents and literature do not mention the use of a multi-step method to prepare a Cu-based catalyst doped with a noble metal and a transition metal for use in the hydrogenation reaction of methyl 3-hydroxypropionate. A Cu-based ester hydrogenation catalyst is prepared by a multi-step method, and different functional additives interact with the main catalyst Cu to form a multi-component composite catalyst with strong interactions, and the reduction ability and species state of Cu are regulated, thereby improving the stability and catalytic performance of the catalyst. Summary of the invention
[0006] In view of the problems of low activity, poor stability and low selectivity of the main product 1,3-propylene glycol of this type of catalyst at present, the present invention provides a Cu-based ester hydrogenation catalyst prepared by a multi-step method and application thereof.
[0007] In order to achieve the above object, the present invention adopts the following technical solution: A Cu-based ester hydrogenation catalyst prepared by a multi-step method comprises the following components: (a) The main component is CuO; (b) Auxiliary agent 1 is one or more of Pt, Pd and Ni; (c) The second additive is one or more of Ge, Sn and Pb of Group IV A; (d) SiO2 as carrier; Calculated by weight percentage and taking 100%, the content of each component is: main component 10-50%, auxiliary agent 1 0.1-10%, auxiliary agent 2 0.01-1%, SiO2 50-90%.
[0008] The preparation method of the Cu-based ester hydrogenation catalyst prepared by the multi-step method comprises the following steps: (1) Dissolve the CuO precursor and the additive precursor in deionized water and stir until the solution becomes transparent; (2) adding 25% by mass of aqueous ammonia to the solution obtained in step (1), and stirring for 2 hours to form a metal complex ion mixed solution; (3) adding hexadecyltrimethylammonium bromide and polyvinylpyrrolidone to the solution obtained in step (2) and stirring for 2 hours; (4) adding an aqueous solution of SiO2 precursor to the solution obtained in step (3), stirring at room temperature for 2 hours, and then aging for 12 hours; (5) Stir the suspension obtained in (4) in a water bath at 80°C for 8 hours. When the pH value of the solution drops below 7, stop heating, filter and wash to obtain a filter cake; (6) dispersing the filter cake obtained in (5) in a deionized water solution of the second additive precursor, stirring at room temperature for 2 hours, and then stirring and evaporating in a 90° C. water bath to obtain a catalyst powder; (7) grinding the catalyst powder obtained in step (6) and drying at 80-150° C. for 6-48 h; (8) calcining the powder obtained in step (7) at 600-1000° C. for 6-48 h under nitrogen; (9) Grinding the powder obtained in step (8), tableting, crushing and sieving to obtain the catalyst.
[0009] Furthermore, the precursor of the main component CuO in step (1) is one or more of copper nitrate, copper sulfate, copper acetate, copper acetylacetonate, and copper chloride.
[0010] Furthermore, the precursor of the auxiliary agent 1 in step (1) is one or more of chloride, nitrate, acetate and sulfate.
[0011] Furthermore, the amount of ammonia water used in step (2) is 5-10 times the total molar amount of CuO and the auxiliary agent.
[0012] Furthermore, in step (3), the amount of hexadecyltrimethylammonium bromide used is 0.1-2.0 times the total molar amount of CuO and the auxiliary agent, and the amount of polyvinylpyrrolidone used is 0.05-1.0 times the total molar amount of CuO and the auxiliary agent.
[0013] Furthermore, the SiO2 precursor in step (4) is tetraethyl orthosilicate, silica sol, or low specific surface area fumed silica.
[0014] Furthermore, the precursor of the auxiliary agent 2 in step (6) is one or more of chloride, nitrate, acetate and sulfate.
[0015] The obtained catalyst can be used for the hydrogenation reaction of methyl 3-hydroxypropionate to 1,3-propylene glycol. The specific operation is as follows: The catalyst loading amount is 10.0 ml. The catalyst is reduced with hydrogen before feeding so that the active component exists in the form of a single substance. The reduction conditions are: temperature 200~450 ℃, pressure 0.1~8.0 MPa, hydrogen flow rate 10~200 ml / min, time 0.5~36h. During the reaction, methyl 3-hydroxypropionate is diluted with methanol, the mass concentration of methyl 3-hydroxypropionate is 5-20%, the temperature is 140-200 ℃, the pressure is 3-8 MPa, the raw material space velocity is 0.01~3.0 h-1, and the hydrogen ester ratio is 200-600.
[0016] The beneficial effects of the present invention are: The present invention uses a multi-step method to prepare a precious metal and transition metal composite doped Cu-based catalyst for the hydrogenation reaction of methyl 3-hydroxypropionate. The catalyst interacts different functional additives with the main catalyst Cu to form a multi-component composite catalyst with strong interaction, regulates the reduction ability and species state of Cu, thereby improving the stability and catalytic performance of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The XRD diagrams of the catalysts of Example 1, Comparative Example 1 and Comparative Example 2 are shown.
[0018] Figure 2 The stability of the catalysts in Example 1 and Comparative Examples 1 and 2 over the reaction time.
[0019] Figure 3H2-TPR diagrams of the catalysts of Example 1 and Comparative Examples 3-5. DETAILED DESCRIPTION
[0020] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0021] Example 1 1.0Ge / 30Cu-0.02Pt / SiO2-AEIM Weigh 17.11 g of copper nitrate trihydrate and 0.008 g of chloroplatinic acid hexahydrate and dissolve them in 100 ml of deionized water, and continue stirring until a transparent solution is obtained; then add 39.78 g of ammonia water (mass fraction 25%) to the solution and stir thoroughly for 2 hours to form a metal complex ion mixed solution; weigh 7.99 g of hexadecyltrimethylammonium bromide (CTAB) and 0.81 g of polyvinylpyrrolidone (PVP) and add them to the above metal complex ion mixed solution, stir thoroughly for 2 hours to form a stable transparent solution; weigh 10.35 g of polyvinylpyrrolidone with a specific surface area of 50 m 2 / g of fumed silica was added to the mixed solution, stirred for 2 hours at room temperature, transferred to a water bath at 80°C and heated for 8 hours until the pH value measured by the pH meter was less than 7, and filtered and washed to obtain a filter cake. 0.44 g of germanium chloride was weighed and dissolved in 200 ml of deionized water to obtain a germanium chloride aqueous solution, the filter cake was added to the germanium chloride aqueous solution, stirred for 2 hours, then placed in a water bath at 90°C and stirred to evaporate to dryness, the evaporated catalyst powder was ground, dried at 120°C for 18 hours, and then calcined at 700°C under nitrogen for 12 hours. The catalyst prepared in this way was recorded as 1.0Ge / 30Cu-0.02Pt / SiO2-AEIM (the value before the component is the percentage of the component content), and after compacting and molding into the above catalyst 1.0Ge / 30Cu-0.02Pt / SiO2-AEIM, it was crushed and sieved into a 14-20 mesh particle catalyst for the test of catalytic performance.
[0022] Example 2 1.0Ge / 30Cu-0.02Pd / SiO2-AEIM Weigh 17.11 g of copper nitrate trihydrate and 0.005 g of palladium chloride and dissolve them in 100 ml of deionized water, and continue stirring until a transparent solution is obtained; then add 39.8 g of ammonia water (mass fraction 25%) to the solution and stir thoroughly for 2 hours to form a metal complex ion mixed solution; weigh 7.99 g of CTAB and 0.81 g of PVP and add them to the above metal complex ion mixed solution, stir thoroughly for 2 hours to form a stable transparent solution; weigh 10.35 g of polyvinyl alcohol with a specific surface area of 50 m 2 / g of fumed silica is added to the mixed solution, stirred for 2 hours at room temperature, transferred to a water bath at 80°C and heated for 8 hours until the pH value measured by the pH meter is less than 7, and filtered and washed to obtain a filter cake. Weigh 0.44g of germanium chloride and dissolve it in 200ml of deionized water. The filter cake is added to the germanium chloride aqueous solution and stirred for 2 hours. Then, it is placed in a water bath at 90°C and stirred to evaporate to dryness. The evaporated catalyst powder is ground and dried at 120°C for 18 hours, and then calcined at 700°C under nitrogen for 12 hours. The catalyst prepared in this way is recorded as 1.0 Ge / 30Cu-0.02Pd / SiO2-AEIM. After compacting and molding into the above 1.0 Ge / 30Cu-0.02Pd / SiO2-AEIM catalyst, it is crushed and sieved into a 14-20 mesh particle catalyst for catalytic performance testing.
[0023] Example 3 1.0Sn / 30Cu-0.02Pt / SiO2-AEIM Weigh 17.11 g of copper nitrate trihydrate and 0.008 g of chloroplatinic acid hexahydrate and dissolve them in 100 ml of deionized water, and continue stirring until a transparent solution is obtained; then add 39.78 g of ammonia water (mass fraction 25%) to the solution and stir thoroughly for 2 hours to form a metal complex ion mixed solution; weigh 7.98 g of CTAB and 0.81 g of PVP and add them to the above metal complex ion mixed solution, stir thoroughly for 2 hours to form a stable transparent solution; weigh 10.35 g of 50 m2 carbonyl chloride with a specific surface area of 50 m 2 / g of fumed silica was added to the mixed solution, stirred for 2 hours at room temperature, moved into a water bath at 80°C and heated for 8 hours until the pH value measured by the pH meter was less than 7, and filtered and washed. Weigh 0.49g of stannous chloride and dissolve it in 200ml of deionized water. The filter cake was added to the aqueous solution of stannous chloride and stirred for 2 hours. Then, it was placed in a water bath at 90°C and stirred to evaporate to dryness. The evaporated catalyst powder was ground and dried at 120°C for 18 hours, and then calcined at 700°C under nitrogen for 12 hours. The catalyst prepared in this way is recorded as 0.8Sn / 30Cu-0.02Pt / SiO2-AEIM. After compacting and molding into the above 0.8Sn / 30Cu-0.02Pt / SiO2-AEIM catalyst, it was crushed and sieved into a 14-20 mesh granular catalyst for catalytic performance testing.
[0024] Example 4 1.0Pb / 30Cu-0.02Pt / SiO2-AEIM Weigh 17.11 g of copper nitrate trihydrate and 0.008 g of chloroplatinic acid hexahydrate and dissolve them in 100 ml of deionized water, and continue stirring until a transparent solution is obtained; then add 39.78 g of ammonia water (mass fraction 25%) to the solution and stir thoroughly for 2 hours to form a metal complex ion mixed solution; weigh 7.98 g of CTAB and 0.81 g of PVP and add them to the above metal complex ion mixed solution, stir thoroughly for 2 hours to form a stable transparent solution; weigh 10.35 g of 50 m 2 / g of fuming silica was added to the mixed solution, stirred for 2 hours at room temperature, moved into a water bath at 80 °C and heated for 8 hours until the pH value measured by the pH meter was less than 7, and filtered and washed. Weigh 0.24 g of lead nitrate and dissolve it in 200 ml of deionized water. The filter cake was added to the aqueous solution of lead nitrate and stirred for 2 hours. Then, it was placed in a water bath at 90 °C and stirred to evaporate to dryness. The evaporated catalyst powder was ground and dried at 120 °C for 18 h, and then calcined at 700 °C under nitrogen for 12 hours. The catalyst prepared in this way is recorded as 1.2Pb / 30Cu-0.02Pt / SiO2-AEIM. After compacting and molding into the above 1.2Pb / 30Cu-0.02Pt / SiO2-AEIM catalyst, it was crushed and sieved into a 14-20 mesh granular catalyst for catalytic performance testing.
[0025] Comparative Example 1 1.0Ge / 30Cu-0.02Pt / SiO2-DP Weigh 17.11 g of copper nitrate trihydrate, 0.008 g of chloroplatinic acid hexahydrate, and 0.44 g of germanium chloride and dissolve them in 100 ml of deionized water. Stir continuously until a transparent solution is obtained to obtain a metal ion mixed solution. Weigh 10.35 g of a 50 m 2 / g of fumed silica is added to the above metal ion mixed solution, and stirred for 1 hour to obtain a metal ion-SiO2 solution; 6.5 g of sodium hydroxide is weighed and dissolved in 100 ml of deionized water, and the sodium hydroxide solution is added dropwise to the above metal ion-SiO2 solution, and stirred at 60 ° C for 4 hours. After precipitation is complete, it is cooled to room temperature, and the formed precipitate is filtered and washed until the residual liquid is neutral. The precipitate obtained by filtration from the above precipitate is dried at 120 ° C for 24 h; the obtained solid is calcined at 700 ° C for 18 h under a nitrogen atmosphere. The catalyst prepared in this way is recorded as 1.0Ge / 30Cu-0.02Pt / SiO2-DP. After compacting and molding into the above 1.0Ge / 30Cu-0.02Pt / SiO2-DP catalyst, it is crushed and sieved into a 14-20 mesh granular catalyst for catalytic performance testing.
[0026] Comparative Example 2 1.0Ge / 30Cu-0.02Pt / SiO2-IMP Weigh 17.11 g of copper nitrate trihydrate, 0.008 g of chloroplatinic acid hexahydrate, and 0.44 g of germanium chloride and dissolve them in 100 ml of deionized water. Stir continuously until a transparent solution is obtained to obtain a metal ion mixed solution. Weigh 10.35 g of a 50 m 2 / g of fumed silica was added to the above metal ion mixed solution, stirred at room temperature for 4 hours, and then transferred to an oil bath at 90 °C and evaporated to remove moisture. The obtained solid was dried at 120 °C for 24 h; the obtained solid was calcined at 700 °C for 18 h in a nitrogen atmosphere. The catalyst prepared in this way was recorded as 1.0 Ge / 30Cu-0.02Pt / SiO2-IMP, and after compacting and molding into the above 1.0 Ge / 30Cu-0.02Pt / SiO2-IMP catalyst, it was crushed and sieved into a 14-20 mesh particle catalyst for the test of catalytic performance.
[0027] Comparative Example 3 30Cu / SiO2-AEIM Weigh 17.11 g of copper nitrate trihydrate and dissolve it in 100 ml of deionized water, and continue stirring until a transparent solution is obtained; then add 38.5 g of ammonia water (mass fraction 25%) to the solution and stir it for 2 hours to form a metal complex ion mixed solution; weigh 7.95 g of CTAB and 0.80 g of PVP and add them to the above metal complex ion mixed solution, stir it for 2 hours to form a stable transparent solution; weigh 10.5 g of a polyvinyl alcohol with a specific surface area of 50 m 2 / g of fumed silica was added to the mixed solution, stirred thoroughly for 2 hours at room temperature, transferred to a water bath at 80°C and heated for 8 hours until the pH value measured by the pH meter was less than 7, filtered and washed. The catalyst powder obtained by filtration was ground and dried at 120°C for 18 hours, and then calcined at 700°C for 12 hours under nitrogen. The catalyst prepared in this way was recorded as 30Cu / SiO2-AEIM, and after compacting and molding into the above 30Cu / SiO2-AEIM catalyst, it was crushed and sieved into a 14-20 mesh granular catalyst for testing catalytic performance.
[0028] Comparative Example 4 30Cu-0.02Pt / SiO2-AEIM Weigh 17.11 g of copper nitrate trihydrate and 0.008 g of chloroplatinic acid hexahydrate and dissolve them in 100 ml of deionized water, and continue stirring until a transparent solution is obtained; then add 39.78 g of ammonia water (mass fraction 25%) to the solution and stir thoroughly for 2 hours to form a metal complex ion mixed solution; weigh 7.99 g of CTAB and 0.81 g of PVP and add them to the above metal complex ion mixed solution, stir thoroughly for 2 hours to form a stable transparent solution; weigh 10.35 g of 50 m2 carbonyl chloride with a specific surface area of 50 m 2 / g of fumed silica is added to the mixed solution, stirred for 2 hours at room temperature, transferred to a water bath at 80°C and heated for 8 hours until the pH value measured by the pH meter is less than 7, and filtered and washed. The filter cake is placed in a water bath at 90°C and stirred to evaporate to dryness. The evaporated catalyst powder is ground and dried at 120°C for 18 hours, and then calcined at 700°C under nitrogen for 12 hours. The catalyst prepared in this way is recorded as 30Cu-0.02Pt / SiO2-AEIM. After compacting and molding into the above 30Cu-0.02Pt / SiO2-AEIM catalyst, it is crushed and sieved into a 14-20 mesh granular catalyst for catalytic performance testing.
[0029] Comparative Example 5 1.0Ge / 30Cu / SiO2-AEIM Weigh 17.11 g of copper nitrate trihydrate and dissolve it in 100 ml of deionized water, and continue stirring until a transparent solution is obtained; then add 39.7 g of ammonia water (mass fraction 25%) to the solution and stir it for 2 hours to form a metal complex ion mixed solution; weigh 7.99 g of CTAB and 0.81 g of PVP and add them to the above metal complex ion mixed solution, stir it for 2 hours to form a stable transparent solution; weigh 10.35 g of polyvinyl alcohol with a specific surface area of 50 m 2 / g of fumed silica is added to the mixed solution, stirred for 1 hour, stirred for 2 hours at room temperature, moved into a water bath at 80°C and heated for 8 hours until the pH value measured by the pH meter is less than 7, and filtered and washed to obtain a filter cake. Weigh 0.44g of germanium chloride and dissolve it in 200ml of deionized water. Add the filter cake to the germanium chloride aqueous solution and stir it for 2 hours. Then place it in a water bath at 90°C and stir to evaporate to dryness. Grind the evaporated catalyst powder, dry it at 120°C for 18 hours, and then calcine it at 700°C under nitrogen for 12 hours. The catalyst prepared in this way is recorded as 1.0 Ge / 30Cu / SiO2-AEIM, compacted and molded into the above 1.0 Ge / 30Cu / SiO2-AEIM catalyst, crushed and sieved into 14-20 mesh granular catalyst for catalytic performance testing.
[0030] Comparative Example 6 1.0Ge / 30Cu-0.02Pt / SiO2-DPIM Weigh 17.11 g of copper nitrate trihydrate and 0.008 g of chloroplatinic acid hexahydrate and dissolve them in 100 ml of deionized water. Stir continuously until a transparent solution is obtained. Add 10.35 g of a 50 m 2 / g of fumed silica, stir thoroughly for 2 hours. Weigh 6.5 g of sodium hydroxide and dissolve it in 100 ml of deionized water to obtain a metal ion-SiO2 solution, add the sodium hydroxide solution dropwise to the metal ion-SiO2 solution, stir at 60 °C for 4 hours, wait for the precipitation to be complete, cool to room temperature, filter and wash the formed precipitate until the residual liquid is neutral. Weigh 0.44 g of germanium chloride and dissolve it in 200 ml of deionized water, add the filter cake to the germanium chloride aqueous solution, stir thoroughly for 2 hours, then place it in a 90 °C water bath, stir and evaporate to dryness, grind the evaporated catalyst powder, dry it at 120 °C for 18 h, and then calcine it at 700 °C for 12 hours under nitrogen. The catalyst prepared in this way is recorded as 1.0 Ge / 30Cu-0.02Pt / SiO2-DPIM. After being compacted into the above 1.0 Ge / 30Cu-0.02Pt / SiO2-DPIM catalyst, it is crushed and sieved into 14-20 mesh granular catalyst for testing of catalytic performance.
[0031] Catalyst evaluation The performance of the catalyst described in any one of the above technical schemes was evaluated in a high-pressure fixed bed reactor using a methanol solution of methyl 3-hydroxypropionate as the reactant. The catalyst loading was 10.0 ml. The catalyst was reduced with hydrogen before feeding, and the reduction conditions were: temperature 320 °C, pressure 6 MPa, hydrogen flow rate 100 ml / min, time 5 h. The reaction conditions were: methyl 3-hydroxypropionate was diluted with methanol to a mass concentration of 5%, temperature 150 °C, pressure 6 MPa, raw material space velocity 0.1 h -1 , hydrogen to ester ratio 500. After 200 hours of reaction, the product of the condensation tank after the reactor was collected, and the raw materials and hydrogenated products were quantitatively and qualitatively analyzed by GC-MC coupling instrument to calculate the conversion rate of 3-hydroxypropionic acid methyl ester hydrogenation reaction and the selectivity of 1,3-propylene glycol. The calculation formula is as follows, and the reaction results are shown in Table 1:
[0032] Table 1 3-HMP conversion rate, 1,3-HMP conversion rate and active metal particle size after 200 h reaction in the examples and comparative examples
[0033] As can be seen from Table 1, by comparing Example 1 with Comparative Example 1 (precipitation method) and Comparative Example 2 (impregnation method), it can be seen that compared with the conventional precipitation method and impregnation method, due to the different properties of each element, the catalyst is prepared by the two-step method, Cu and the auxiliary agent 1 are easy to form soluble complex ions, and high dispersion can be achieved. Under this condition, the auxiliary agent 2 is easy to directly form precipitation, which affects the loading effect, so the auxiliary agent 2 is loaded by the impregnation method. The particle size of the main active species Cu is still small after 200h of reaction, and the active metal dispersion is high ( Figure 1), the additive and the active metal easily form a strong interaction, the catalyst has high performance, and the catalyst activity remains high after running for 200 h, and the stability is better ( Figure 2 ).
[0034] By comparing Example 1 with Comparative Examples 3, 4 and 5, it can be seen that the doping of the additive affects the reduction properties of the Cu catalyst. The H2-TPR experiment ( Figure 3 ) indicates that the Ge doping suppresses the reduction of Cu and causes the reduction peak to move to higher temperatures, the Pt doping improves the reducibility of Cu, and the double doping can better balance the Cu in the active species. 0 and Cu I ratio, thereby improving the selectivity of the main product 1,3-propylene glycol in the catalyst.
[0035] In addition, IVA group Ge, Pb, Sn and silicon are homologous compounds, and they form CuGeOx, CuSnOx and CuPbOx composite oxides with Cu during the catalyst formation process, thereby inhibiting the reduction of Cu. A portion of Cu is easily formed into Cu2O state, which is conducive to ester group adsorption and improves selectivity. Adding Pt / Pd / Ni elements forms a partial alloy phase with Cu, which is conducive to the activation of hydrogen. In the H2-TPR experiment, a three-peak structure is formed in Example 1, which also shows the interaction between Cu-Ge-Pt.
[0036] By comparing Examples 1, 2, 3, and 4, it can be seen that the doping of additives Ge and Pt is more helpful in controlling the particle size of Cu, and the catalyst has better 3-hydroxypropionic acid methyl ester conversion rate and product selectivity.
[0037] By comparing Example 1 and Comparative Example 6, it can be seen that when Cu is combined with platinum group elements, ammonia is used to form a uniform complex ammonia ion mixed solution. Compared with the precipitation method, the synthesis method of the present invention is more helpful to enhance the interaction and dispersion effect of Cu with Pt and Ge, thereby improving the catalyst performance.
[0038] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A Cu-based ester hydrogenation catalyst prepared by a multi-step process, characterized in that: Includes the following components: (a) The main component is CuO; (b) Auxiliary agent 1 is one or more of Pt, Pd and Ni; (c) The second additive is one or more of Ge, Sn and Pb of Group IV A; (d) SiO2 as carrier; Calculated by weight percentage and taking 100%, the content of each component is: main component 10-50%, auxiliary agent 1 0.1-10%, auxiliary agent 2 0.01-1%, SiO2 50-90%.
2. The method for preparing a Cu-based ester hydrogenation catalyst according to claim 1, wherein The steps include: (1) Dissolve the CuO precursor and the additive precursor in deionized water and stir until the solution becomes transparent; (2) adding 25% by mass of aqueous ammonia to the solution obtained in step (1), and stirring for 2 hours to form a metal complex ion mixed solution; (3) adding hexadecyltrimethylammonium bromide and polyvinylpyrrolidone to the solution obtained in step (2) and stirring for 2 hours; (4) adding an aqueous solution of SiO2 precursor to the solution obtained in step (3), stirring at room temperature for 2 hours, and then aging for 12 hours; (5) Stir the suspension obtained in (4) in a water bath at 80°C for 8 hours. When the pH value of the solution drops below 7, stop heating, filter and wash to obtain a filter cake; (6) dispersing the filter cake obtained in (5) in a deionized water solution of the second additive precursor, stirring at room temperature for 2 hours, and then stirring and evaporating in a 90° C. water bath to obtain a catalyst powder; (7) grinding the catalyst powder obtained in step (6) and drying at 80-150° C. for 6-48 h; (8) calcining the powder obtained in step (7) at 600-1000° C. for 6-48 h under nitrogen; (9) Grinding the powder obtained in step (8), tableting, crushing and sieving to obtain the catalyst.
3. The preparation method according to claim 2, characterized in that: The precursor of the main component CuO in step (1) is one or more of copper nitrate, copper sulfate, copper acetate, copper acetylacetonate and copper chloride.
4. The preparation method according to claim 2, characterized in that: The precursor of the auxiliary agent 1 in step (1) is one or more of chloride, nitrate, acetate and sulfate.
5. The preparation method according to claim 2, characterized in that: The amount of ammonia water used in step (2) is 5-10 times the total molar amount of CuO and the additive.
6. The preparation method according to claim 2, characterized in that: In step (3), the amount of hexadecyltrimethylammonium bromide used is 0.1-2.0 times the total molar amount of CuO and the auxiliary agent, and the amount of polyvinylpyrrolidone used is 0.05-1.0 times the total molar amount of CuO and the auxiliary agent.
7. The preparation method according to claim 2, characterized in that: The SiO2 precursor in step (4) is tetraethyl orthosilicate, silica sol, or low specific surface area fumed silica.
8. The preparation method according to claim 2, characterized in that: The precursor of the auxiliary agent 2 in step (6) is one or more of chloride, nitrate, acetate and sulfate.
9. Use of the catalyst as claimed in claim 1 in hydrogenating methyl 3-hydroxypropionate to produce 1,3-propylene glycol.
Citation Information
Patent Citations
Method for preparing 1,3 propanediol by 3-methyl lactate
CN101993352A
Catalyst for preparing 1,3-propanediol by hydrogenating methyl 3-hydroxypropanoate
CN102059125A
Catalytic agent for preparing 1,3-PDO by performing hydrogenization on 3-hydracrylic acid methyl ester, and preparation and application of catalytic agent
CN103721734A
An ester hydrogenation catalyst, its preparation method and application
CN107303488B
A supported binary metal catalyst, its preparation method and its application
CN114345339B